POLA PENCUCIAN UANG HASIL PERDAGANGAN NARKOBA DAN PEMBALAKAN LIAR - Lucky Nurhadiyanto (Jurnal Kriminologi Indonesia, 2010)
This research discuss about the distribution and development in money laundering models of drugs trafficking and illegal logging. The distribution in money laundering model of drugs trafficking and illegal logging is divided into three phase, there are placement, layering and integration. The phase includes placing activity of illegal money into finance system, layering them through various finance transaction and integrating the money into legitimate bussines. The trend of that model is based on: first, the techniques of money laundering become more sophisticated because progressive separation between criminal activities and money laundering activities; second, the professional involvement become luster involve more professional launderers such as accountants, lawyers, private bankers; and third, the provision of money laundering services to a wide range of criminals and to more than one criminal organization.